Immediate Effects of Aerobics on Mental Well-being of Primary Resource Teachers in Kerala - James, Jasmin; George, Augustine; K P, Prashobhith (JOURNAL OF INDIAN EDUCATION, 2023)
Mental well-being of primary teachers is an important yardstick to impart quality teaching learning activities to the elementary students. Many studies suggest that teaching is a difficult job with high burn out rates. This is in addition to other COVID-19 related adjustments and responsibilities in their family, society and institution. The study aims to know the immediate effect of aerobics on mental well-being of primary resource teachers. The study was conducted at a state level training programme for Kerala state primary resource teachers group at Munnar, Kerala. Experimental design was used for the study. 80 resource teachers (F=40 and M=40) aged between 26 and 55 from state resource group (SRG) of primary teachers of Kerala were selected for this study. The teachers interested in aerobics were included into experimental group (n=41), and teachers who lack interest or were unfit for physical activity were put in control group (n=39). Both groups were tested to analyse mental well-being using Warwick Edinburg Mental Well-being Scale. Experimental group were made to do moderate intensity aerobic dance immediately after the pre-test and the control group were left alone. Post-test were conducted to find if there is any significant difference in the experimental group following paired sample ‘t’ test and the results demonstrated significant difference at 0.05 level. Experimental group shows increase in their mental well-being score (p<0.01), whereas control group didn’t show any difference in mental well-being, (p=0.135) which implies that aerobics could be a good intervention even in short run to improve the mental well-being among primary teachers.